Prototype-Scale Physical Model of Wave Attenuation Through a Mangrove Forest of Moderate Cross-Shore Thickness: LiDAR-Based Characterization and Reynolds Scaling for Engineering With Nature - Kelty, Kiernan; Tomiczek, Tori; Cox, Daniel Thomas; Lomonaco, Pedro; Mitchell, William (Frontiers in Marine Science, 2022)
This study investigates the potential of a Rhizophora mangrove forest of moderate cross-shore thickness to attenuate wave heights using an idealized prototype-scale physical model constructed in a 104-m long wave flume. An 18-m long cross-shore transect of an idealized red mangrove forest trunk-prop root system was constructed in the flume. Two cases with forest densities of 0.75 and 0.375 stems/m2 and a third baseline case with no mangroves were considered. LiDAR was used to quantify the projected area per unit height of the model forest and estimate the effective diameter of the system. The methodology was accurate to within 2% of the known stem diameters and 10% of the known prop root diameters. Random and regular wave conditions seaward, throughout, and inland of the forest were measured to determine wave height decay rates and drag coefficients for wave conditions and water depths in the range 0.36 < kh < 1.44. Wave height decay rates ranged 0.008 m-1 to 0.021 m-1 for the high density cases and 0.004 m-1 to 0.010 m-1 for the low density cases and were found to be a function of the water depth. Doubling the forest density increased the decay rate by a factor two. Drag coefficients ranged 0.4 to 3.8, and were found to be dependent on the Reynolds number. The uncertainty in the estimates of CD due to the measured projected area and measured wave attenuation were quantified and found to have average combined standard deviations of 0.58 and 0.56 for random and regular waves, respectively. Two previous reduced-scale studies of wave attenuation by mangroves compared well with the present study when their Reynolds numbers were re-scaled by λ3/2 where λ is the prototype to model geometric scale ratio. Using the combined data sets, an equation is proposed to estimate the drag coefficient for a Rhizophora mangrove forest: CD = 0.6 + 3e4/ReDBH with an uncertainty of 0.69 over the range 5e3 < ReDBH < 1.9e5, where ReDBH is based on the diameter at breast height. Results may improve engineering guidance for the use of mangroves and other emergent vegetation in coastal wave attenuation.